Curbing antimicrobial resistance: Do physicians receive adequate education about antibiograms?. Issue 1 (January 2016) - Nand, Priyasheelta; Wilson, Machelle D.; Cohen, Stuart H.; Brown, Jennifer
Highlights: Antibiotic overuse is driving the worldwide crisis of antimicrobial resistance. All health care workers must become skilled in appropriate antimicrobial prescribing. The WHO recommends the use of antibiograms to guide antimicrobial prescribing. Physicians are not receiving adequate education about antibiograms.